Modules on problem solving for second year high school students - Cachero, Ma. Concepcion Molano (Animo Repository, 1994)
This study generates the development and evaluation of modules for enhancing problem-solving skills in Math for second year high school students of the University of Santo Tomas, SY 1994-1995.The study utilized two intact classes of high school sophomores. From a population of 98 students, only 60 students were chosen. They were matched and equated according to sex, age, grade in Mathematics I, pretest scores, and results of Otis-Lennon Mental Ability Test. Thirty students from a randomly chosen intact class composed the experimental group that was exposed to modular instruction. Thirty students from the other intact class, the control group, was exposed to the traditional lecture-discussion method.The descriptive-developmental method of research was used in the development of the modules. The quasi-experimental method with the pretest-posttest design was used in the evaluation of the modules. An aptitude test, an achievement test, and two questionnaires for the evaluation of the modules were the instruments used in this study. The data gathered in the study were tabulated and analyzed using the mean, standard deviation and the t-test. The following findings were arrived at: 1. The second year high school students encountered difficulties in (a) translating word phrases/sentences to algebraic expressions/equations, (b) transforming and solving equations, and (c) acquiring the necessary technique for solving word problems. They could relate to problems involving percent/discount, number relations, grade computation, financial budgeting, and time management 2. The teachers gave a highly favorable rating for the modules. The students rated the modules to be favorable and,3. Although the students learned after being exposed to either the modular instruction or the lecture-discussion method, more learning took place when the students were exposed to the modular approach. The following conclusions were made:1. Majority of the second year high school students recognized the need for additional learning aids in acquiring the skills in problem-solving 2. The teachers and the students found the prepared modules readable and possessing a highly favorable degree of content validity and reliability and,3. Students who used the modules performed better than those who were exposed to the traditional lecture-discussion method of instruction.